Manajemen Laba : Analisis Good Corporate Governance pada Perusahaan Teknologi Periode 2019-2022: GCG - Surya, Iwan Juni; Prastya, Hendra; Mazwini, vina (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2024)
ABSTRACT Profit management is one of the deliberate processes of taking steps within the limits of generally accepted accounting principles both within and outside the limits of General Accepted Accounting Principles (GAAP). While this study aims to determine the effect of Good Corporate Governance on Profit Management. This research was conducted on 23 companies that are members of DES for the 2019-2022 period. . The study used secondary data derived from the publication of the company's annual report which was downloaded through www.ojk.go.id. Data analysis using panel data regression with the help of EVIEWS. The results of the study are that the audit committee has a negative effect on profit management, while the age of commissioners and independent commissioners has a positive effect on profit management, Simultaneously the audit committee, the age of the commissioner and the independent commissioner have a positive effect on profit management. Keywords : Profit Management, Corporate Good Governance (GCG), Audit Committee, Age of Commissioners, Independent Commissioner, EVIEWS